Nurse Managers’ Responsive Coaching To Facilitate Staff Nurses’ Clinical Skills Development in Public Tertiary Hospital - Alfonso, Anna Liza R; Hipona, Jocelyn B.; Quijencio, Wilfredo (Journal Of Nursing Practice, 2021)
Background: Mentoring helps cultivate nurse leaders, retain nurses, and diversify the nursing workforce. By strengthening the nursing workforce, nursing mentorship improves the quality of patient care and outcomes. Widespread uses of nurse mentoring programs have been employed to produce positive outcomes and decrease turnover and assess job satisfaction.Purpose: The purpose of the study is to assess head nurse mentoring competency in relation to staff nurses’ career advancement in selected government hospitals to broaden the array of perspective among public hospitalsMethods: The researchers employed descriptive-correlational that glanced into the relationship of certain levels in the mentoring competency of head nurses in relation to staff nurses career advancement.Results: Majority of the nurse-respondents have indicated good remarks on the components of relationship building in public hospitals; and very good competency on the components of identifying areas for improvement; responsive coaching; advocating for an environment conducive to good patient care; and documentation/record keeping.  Conclusion: Nurse manager-mentors in public hospitals are very good on mentoring in identifying areas for improvement, responsive coaching, advocating for an environment conducive to good patient care, and documentation/record keeping, but, good about relationship building.